Sexual harassment of women in the workplace: a systematic review - Roberta de Lima; Fabiana B. Caldas; Breno de O. Ferreira; Ronaldo Gomes-Souza (Psicologia: Teoria e Pesquisa, 2025)
Abstract Sexual harassment was classified as a crime by Law No. 10,224/2001, marking an important milestone in combating this form of violence. This systematic review analyzed how scientific investigations on sexual harassment at work in Brazil have evolved over the past two decades. The research led to the selection of 17 publications. In the analysis of the manuscripts, it was identified that sexual harassment has women as the primary victims of this type of violence, bringing consequences for the mental health and professional development of the victims. The research shows that law does not fully cover the power and gender relations experienced by female workers.